Trust, Faith, and Market: The Dualism of Indonesian Food Halal Certification between Self-Declaration and Global Standards - Ayu Citra, Ken; Hidayat, Rahmat; Nurwahidin, Nurwahidin; Hannase, Mulawarman; Warto’i, Warto’i (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Halal certification in the food industry is not merely an administrative matter but represents a sharia mandate (faith), an instrument for building and maintaining consumer trust (trust), and a vital asset in strengthening Indonesia’s position in the global market (market). As the world’s largest Muslim-majority country, Indonesia holds a strategic potential to become the global hub of the Halal Food Industry. However, since the enactment of Law No. 33 of 2014 on Halal Product Assurance (JPH Law), a dilemma has emerged due to the dualism of certification pathways: the regular system (through BPJPH–MUI–LPH) and the self-declare system designated for micro and small enterprises (MSEs). Employing a qualitative approach grounded in literature reviews, regulatory analysis, and Halal Food Industry reports, this study integrates a SWOT analysis to assess the strategic position of Indonesia’s halal certification policy. The findings reveal that the strengths of Indonesia’s halal system lie in its large Muslim demographic base and strong foundation of sharia spirituality; weaknesses arise in issues of credibility, halal literacy among MSE actors, and fragmented governance structures; opportunities exist in the economic inclusivity of MSEs, the digitalization of certification via the SIHALAL platform, and the potential for global halal diplomacy; while threats include the risks of halal washing, commodification of halal values, and disharmony with international standards. This study concludes that for Indonesia to realize its vision of becoming the global center of the Halal Food Industry, an integrated policy framework is needed one that harmonizes spiritual aspects (faith), public trust (trust), and global market credibility (market) within a competitive and internationally recognized Halal Integrity System.